Forecasting equity returns: The role of commodity futures along the supply chain. Issue 1 (17th October 2020) - Li, Chenchen; Wu, Chongfeng; Zhou, Chunyang
Abstract: This paper examines equity return predictability using the returns of commodity futures along the supply chain in China's financial market. We find that a considerable number of commodities exhibit significant in‐sample forecasting ability at the daily horizon, especially for supplier‐side equity returns. The macroeconomic risk premium effect, captured by the aggregate commodity prices, is an important source for this predictability. The out‐of‐sample results show that for most commodities, the predictability remains both statistically and economically significant, and the forecasting performance improves substantially during recessions or with economic constraints.